Atypical antipsychotics: trends in analysis and sample preparation of various biological samples. (April 2012) - Fragou, Domniki; Dotsika, Spyridoula; Sarafidou, Parthena; Samanidou, Victoria; Njau, Samuel; Kovatsi, Leda
Atypical antipsychotics are increasingly popular and increasingly prescribed. In some countries, they can even be obtained over-the-counter, without a prescription, making their abuse quite easy. Although atypical antipsychotics are thought to be safer than typical antipsychotics, they still have severe side effects. Intoxications are not rare and some of them have a fatal outcome. Drug interactions involving atypical antipsychotics complicate patient management in clinical settings and the determination of the cause of death in fatalities. In view of the above, analytical strategies that can efficiently isolate atypical antipsychotics from a variety of biological samples and quantify them accurately, sensitively and reliably, are of utmost importance both for the clinical, as well as for the forensic toxicologist. In this review, we will present and discuss novel analytical strategies that have been developed from 2004 to the present day for the determination of atypical antipsychotics in various biological samples.